The Study of Methods for Penetration Testing in Training of Information Security Specialists - A. M. Kadan; A. K. Doronin (Цифровая трансформация)
The article deals with issues related to the creation of modern educational virtual laboratory under cloud cluster platform OpenNebula for the training of specialists in the field of information security and computer security. The use of such laboratories allows teaching methods of penetration testing on examples of objects of different levels of difficulty, and also provides the possibility of rapid changes in infrastructure and characteristics of the objects.